2001
DOI: 10.1200/jco.2001.19.8.2201
|View full text |Cite
|
Sign up to set email alerts
|

Oral Mucositis and the Clinical and Economic Outcomes of Hematopoietic Stem-Cell Transplantation

Abstract: Oral mucositis is associated with significantly worse clinical and economic outcomes in blood and marrow transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
391
2
41

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 591 publications
(449 citation statements)
references
References 8 publications
15
391
2
41
Order By: Relevance
“…1 This second analysis of data from this pan-European audit provides new insights into the clinical sequelae of severe OM and associated medical resource use. Consistent with other observations, 8,13 we found that severe OM was closely related to development of fever, with the incidence of fever being 21% higher and the duration of fever 1.2 days longer, in those with severe OM. Previous studies in the SCT setting have shown that the risk of fever and/or febrile neutropenia (FN) increases with increasing grade of OM.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…1 This second analysis of data from this pan-European audit provides new insights into the clinical sequelae of severe OM and associated medical resource use. Consistent with other observations, 8,13 we found that severe OM was closely related to development of fever, with the incidence of fever being 21% higher and the duration of fever 1.2 days longer, in those with severe OM. Previous studies in the SCT setting have shown that the risk of fever and/or febrile neutropenia (FN) increases with increasing grade of OM.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies in the SCT setting have shown that the risk of fever and/or febrile neutropenia (FN) increases with increasing grade of OM. 8,9 Moreover, the recombinant growth factor palifermin, which protects the oral mucosa from damage induced by myelotoxic-conditioning treatment, was able to reduce the risk of FN in patients undergoing SCT. 14 The association of fever with oral mucositis has been attributed to local and systemic infections, as disruption of the mucosal barrier may provide an entry point for pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations